The predictive significance of physical and mental components of health related quality of life questionnaire SF-36 in adults with congenital heart disease - Lebid, I. H. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Introduction. The estimation of health related quality of life (HRQoL) should determine the impact of the disease and its treatment on the psychological, emotional status adults with congenital heart disease (ACHD). The purpose was to evaluate HRQoL and estimate the prognostic significance of the physical and mental components of health. Material and Methods. There were 456 consecutive ACHD that comprised the main group and 79 healthy adults in the control group. HRQoL was evaluated by SF-36 questionnaire. Results and discussion. Indices of physical health (PH – 49.0±0.4) and mental health (MH – 48.2±0.5) in ACHD were worse compared to the control group (52,8±0.7 and 51.3±0.8, respectively, p<0.05). Female with CHD PH – 47.6±07 and MH – 46.5±0.7 were lowered compared to men (50.5±0.6 and 49.8±0.7, p<0.05). Conclusions. Congenital heart disease in adults are heterogeneous nosology with a wide range of pathology, different level of complexity and prognosis for the follow-up. There were presented prognostic significance the physical and mental components of HRQoL changes, with good indices in young adults, and worse indicators with age increasing. Female with CHD had worse indices of physical and mental components of HRQoL that had a prognostic gender addiction.